ChemInform Abstract: Catalytic Staudinger/Aza‐Wittig Sequence by in situ Phosphane Oxide Reduction. Issue 13 (1st April 2014) - van Kalkeren, Henri A.; te Grotenhuis, Colet; Haasjes, Frank S.; Hommersom, C. A.; Rutjes, Floris P. J. T.; van Delft, Floris L.
Abstract A Staudinger/aza‐Wittig process using catalytic amounts of 5‐phenyldibenzophosphole is described.